2012
DOI: 10.1089/ast.2012.0840
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities and the Nitrogen Cycle in the Gypsum Soils of Cuatro Ciénegas Basin, Coahuila: A Mars Analogue

Abstract: The OMEGA/Mars Express hyperspectral imager identified gypsum at several sites on Mars in 2005. These minerals constitute a direct record of past aqueous activity and are important with regard to the search of extraterrestrial life. Gale Crater was chosen as Mars Science Laboratory Curiosity's landing site because it is rich in gypsum, as are some desert soils of the Cuatro Ciénegas Basin (CCB) (Chihuahuan Desert, Mexico). The gypsum of the CCB, which is overlain by minimal carbonate deposits, was the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 63 publications
6
45
4
Order By: Relevance
“…However, the sites analyzed in this study differed in diversity, with soil adjacent to the River being more diverse than the Dry Lagoon if we compare the OTUs at 97% (Table 4). In the previous clone library study the same pattern was observed (López-Lozano et al, 2012). We also evaluated the community composition in terms of “ecological groups”, considering groups in which abundance correlated with high or low C mineralization rates (copiotrophs or oligotrophs, respectively) in general soil surveys (Fierer, Bradford & Jackson, 2007; Fierer et al, 2010), and widely known autotrophs (phototrophs such as Cyanobacteria and Chloroflexi).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, the sites analyzed in this study differed in diversity, with soil adjacent to the River being more diverse than the Dry Lagoon if we compare the OTUs at 97% (Table 4). In the previous clone library study the same pattern was observed (López-Lozano et al, 2012). We also evaluated the community composition in terms of “ecological groups”, considering groups in which abundance correlated with high or low C mineralization rates (copiotrophs or oligotrophs, respectively) in general soil surveys (Fierer, Bradford & Jackson, 2007; Fierer et al, 2010), and widely known autotrophs (phototrophs such as Cyanobacteria and Chloroflexi).…”
Section: Discussionsupporting
confidence: 79%
“…The dominant soil is gypsisol, and the predominant vegetation types are halophile and gypshophile grasses. As described before (López-Lozano et al, 2012), the Churince system consists of a spring, an intermediate lagoon, and a desiccation lagoon (Dry Lagoon), connected by short shallow creeks. Two sites separated by one kilometer were selected.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Near-zero concentrations of dissolved inorganic P have been recorded in grassland (Lo´pez-Lozano et al 2012) and in the aquatic system of the valley (ca. Near-zero concentrations of dissolved inorganic P have been recorded in grassland (Lo´pez-Lozano et al 2012) and in the aquatic system of the valley (ca.…”
Section: Introductionmentioning
confidence: 99%